Comparative study of defect mode intensity and wavelength modulation in Bragg fiber waveguide sensors - Chourasia R.K.; Singh Yadav C.; Upadhyay A.; Chourasia N.K.; Singh V. (My University, 2025)
Sensing parameters of Bragg fiber waveguides having a defect layer in the cladding region are studied theoretically for bio-sensing and thickness monitoring applications. A comparison between Bragg fiber waveguides consist of a liquid-core surrounded with alternate high refractive index (R.I.) contrast of claddings and low R.I. contrast of claddings is presented. In non-homogeneous multilayer cylindrical system, the transmittance of proposed waveguide-based sensors is formulated using transfer matrix method and Hankel formalism. Both considered structures show photonic bandgap with a narrow passband in the bandgap region. This narrow passband is treated as sensing signal because its position and intensity depends on the diameter and refractive index of core material. The high refractive index contrast cladding waveguide shows larger intensity shift than low refractive index contrast cladding waveguide. The presence of defect layer in both considered waveguides is able to increase the sensing parameters like detection accuracy and overall performance. © 2020 Elsevier GmbH